2021
DOI: 10.3389/fimmu.2021.638435
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Consequences of In Utero Exposure to Foreign Antigens

Abstract: Immunologic tolerance refers to a state of immune nonreactivity specific to particular antigens as an important issue in the field of transplantation and the management of autoimmune diseases. Tolerance conceptually originated from Owen’s observation of blood cell sharing in twin calves. Owen’s conceptual framework subsequently constituted the backbone of Medawar’s “actively acquired tolerance” as the major tenet of modern immunology. Based upon this knowledge, the delivery of genetically distinct hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Prenatal influences on immunobiography include numerous aspects, such as the health of future parents before conception, genetic predisposition, demographic and economic determinants, maternal health during pregnancy, and influences of the uterine environment and maternal biopsychic and cultural organisms during pregnancy 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal influences on immunobiography include numerous aspects, such as the health of future parents before conception, genetic predisposition, demographic and economic determinants, maternal health during pregnancy, and influences of the uterine environment and maternal biopsychic and cultural organisms during pregnancy 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Fetuses develop immune tolerance to self-antigens and maternal antigens while growing in the maternal uterus 34). Attempts have been made to induce tolerance to foreign antigens by transplanting them during the fetal period, but the degree of tolerance acquisition varies, and consistent results have not been obtained 35,36,37). In the allogeneic transplantation in this study, the difference in the degree of tolerance may have influenced the difference in the degree of urine production.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve in vivo organ generation in the future, studying the mechanisms by which human cells are rejected from animal embryos and developing strategies for efficiently transplanting human donor cells into animal embryos is essential. Previous studies have shown that the innate immune system plays an essential role in xenotransplantation (Azimzadeh et al, 2015; Chen, 2021; Ide et al, 2007) and that the contribution of human cells can be increased by suppressing their apoptosis (Zheng et al, 2021). However, as shown in the current study, phenomena caused by distant interspecies chimerism, such as developmental abnormalities caused by the injection of an excess number of human cells, are poorly understood.…”
Section: Discussionmentioning
confidence: 99%